Streptococcus pneumoniae capsule determines disease severity in experimental pneumococcal meningitis. Issue 3 (March 2016) - Hathaway, Lucy J.; Grandgirard, Denis; Valente, Luca G.; Täuber, Martin G.; Leib, Stephen L.
Abstract : Streptococcus pneumoniae bacteria can be characterized into over 90 serotypes according to the composition of their polysaccharide capsules. Some serotypes are common in nasopharyngeal carriage whereas others are associated with invasive disease, but when carriage serotypes do invade disease is often particularly severe. It is unknown whether disease severity is due directly to the capsule type or to other virulence factors. Here, we used a clinical pneumococcal isolate and its capsule-switch mutants to determine the effect of capsule, in isolation from the genetic background, on severity of meningitis in an infant rat model. We found that possession of a capsule was essential for causing meningitis. Serotype 6B caused significantly more mortality than 7F and this correlated with increased capsule thickness in the cerebrospinal fluid (CSF), a stronger inflammatory cytokine response in the CSF and ultimately more cortical brain damage. We conclude that capsule type has a direct effect on meningitis severity. This is an important consideration in the current era of vaccination targeting a subset of capsule types that causes serotype replacement.